Diseño de una planta productora de aceite a base de semillas de maracuya, en la empresa TROPIFRUTAS S.A. - Moreira Intriago, Jean Carlos, (2018)
The following research project is focused on the design of an oil seed plant based on passion fruit seeds that would be implemented in the company Tropifrutas S.A, to take advantage of this way the generation of waste that the plant produces. Tropifrutas S.A is a company with great experience in the country elaborating products derived from passion fruit. The oil based on passion fruit seeds has different uses which are intended for the manufacture of cosmetics for topical use and applied to by-products to be made with it, such as: restorative creams, massage oils, make-up remover oils, anti-acne creams, among others. Prior to the design, the theoretical methods of extracting oils are investigated to take the alternative that best suits the needs of the company. Effect to the alternatives proposed, it was decided to choose the extraction by cold pressing, because one of the main guidelines proposed by the representatives of the company is, the non-use of chemicals for the extraction of the product. A technical study was elaborated taking into consideration the different equipment necessary for the production and available in the current market, the production capacity of the company's waste (seeds), the way to develop the activities in the plant, labor required, plant distribution, among others. Then an economic-financial study was carried out, determining each of the implementation costs, calculating an item as initial investment of $ 78.220,01 for its implementation. In the economic-financial study, techniques such as the VAN and the TIR were applied, tools that helped to evaluate the viability of the project.